EFEKTIVITAS EKSTRAK DAUN KERSEN (Muntingia calabura L.) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL TIKUS PUTIH JANTAN (Rattus norvegicus L.) YANG DIINDUKSI PAKAN TINGGI LEMAK - Cornelia Ayu Putri; Yuliet Yuliet; Khildah Khaerati (Biocelebes, 2018)
Muntingia calabura L. leaves contains saponin and flavonoid that can reduce blood cholesterol levels. This study aimed to examine the effect and the effective dose of M. calabura L. leaves extract to decrease total cholesterol levels of white rats induced by high-fat diet. Extract was found by using ethanol 96% in maseration method. Before doing a different treatment , all the subjects were given a high-fat meal for 14 days to increase the blood total cholesterol levels. The subject were twenty five rats divided into 5 groups as follow: negative control (0.5% Na-CMC), positive control (Simvastatin 1.8 mg/200 g BW), ethanol M. calabura L. leaves extract in various concentration (50; 100; 150 mg/kg BW). All rats were given a different oral treatment for 14 days. Rats blood was taken to measure total cholesterol levels by using Nesco Multicheck Tester on the 7th day after acclimatization, the 14th day after high-fat food induced, and the 7th and 14th day after treatments. The data was analized using non parametric Kruskal Wallis and Mann Whitney statistical test at α = 0.05. The results showed that the ethanol extract of M. calabura L. leaves have an effect to decrease blood total cholesterol levels and the most effective dose to decrease total cholesterol levels were 50 mg/kg BW.